Asset management excellence : optimizing equipment life-cycle decisions - Campbell, John D.; McGlynn, Joel (CRC Press, 2011)
Globalization, consolidation, and changes in technology challenge asset management and maintenance professionals to be more efficient. This book provides coverage of leadership issues, the implementation of new processes, and change management